Program Kemitraan Masyarakat bagi Kelompok Kader Kesehatan Ibu Hamil dalam Implementasi Program Pendampingan Kehamilan di Wilayah Puskesmas Arjowinangun Malang - Gita Kostania; Rita Yulifah; Suprapti Suprapti (Jurnal Empathy Pengabdian Kepada Masyarakat, 2024)
Background: Pregnancy in a woman is a physiological process, but there is a risk of experiencing pregnancy complications. Many influencing factors, both direct and indirect, can cause maternal death. In 2021, pregnancies with risks at the Arjowinangun Community Health Center were 335 (43.96%). One of the programs carried out to overcome maternal mortality is "assistance for pregnant women based on community empowerment". This mentoring activity is carried out by involving health cadres by implementing motivational, educational, and reporting functions. Methods: The activity implementation method consists of: preparation, implementation and evaluation stages. The implementation phase consists of: cadre training activities, and three times assisting pregnant women in the Arjowinangun Community Health Center area, Malang. The number of accompanying cadre participants was 28 cadres, with the supervision of 4 regional midwives. Knowledge before and after training averaged 81.00 and 88.30. Meanwhile, cadre skills in mentoring activities before and after training were 74.30 and 87.50. Results: The results of the assistance attended by pregnant women with an average age of 20-35 years (75%), gravida secundi (39.29%), with a high risk of pregnancy (78.57%) by looking at the pre-test and post-test scores the mentoring test is 75.50 and 87.80, for the knowledge indicator. At the end of pregnancy and postpartum period, there were no complications both mothers and babies (100%). Conclusion: refreshing material for cadres, as well as assistance by trained personnel to health cadres in the pregnancy assistance program is needed for optimal assistance results for pregnant women.